STUDENT READING ANXIETY OF ENGLISH LEARNING CLASS AT XI GRADE - Rianawati, Devi; Pradana, Dian Arief; Anwar, Saiful; Pambayun, Rizki Nurfida (FKIP Unismuh Makassar, 2024)
This study investigates the factors contributing to reading anxiety among eleventh-grade students learning English as a foreign language at MA NW Islamic High School. Utilizing a qualitative research approach, the researchers conducted observations and interviews to gather in-depth insights into students' experiences and perceptions of reading anxiety. The data analysis process, guided by the framework established by Matthew B. et al. (2014), involved data reduction, visualization, inference, and validation to identify key themes and patterns. The findings indicate that 60% of the students’ exhibited signs of anxiety during reading activities, with significant sources of this anxiety including fear of making mistakes, challenges in understanding complex texts, and difficulties with unfamiliar vocabulary. Emotional responses such as embarrassment and self-consciousness were also prevalent, further exacerbating students' reluctance to engage in reading tasks. The study highlights the critical need for educators to recognize and address these anxiety-inducing factors, thereby fostering a supportive learning environment that enhances students' confidence and competence in reading English texts. Addressing reading anxiety is essential for improving students' learning outcomes in English language education. By implementing tailored interventions and support strategies, educators can help mitigate anxiety levels, promote effective reading practices, and ultimately enhance students' overall academic performance. This research underscores the importance of creating a nurturing educational atmosphere that empowers students to overcome their reading challenges and succeed in their language learning journey.